Analysis of the Relationship between Knowledge of Adolescent Girls and Cervical Cancer Prevention Efforts in Class X of Dharma Bakti Private High School, Tanah Jawa, Simalungun Regency - Saragih, Astri Ulina; Purba, Yeni Trisna; Halawa, Lidwina Priskahati (International Journal of Public Health Excellence (IJPHE), 2022)
Cervical cancer is the most common gynecological disease. It's a disease feared by all women because it's the leading cause of death among women in developing countries, including Indonesia. From the results of the study on the relationship between the knowledge of young women and efforts to prevent cervical cancer in Class X of Dharma Bakti Private High School, Tanah Jawa, Simalungun Regency, the following conclusions can be drawn: Young women in Class X of Dharma Bakti Private High School, Tanah Jawa, Simalungun Regency have good knowledge, this is indicated by the frequency distribution of the level of knowledge of young women about cervical cancer, 39 respondents (78%) who know the causes, methods of transmission, symptoms, development, examination, treatment, and efforts to prevent cervical cancer, while the level of knowledge of young women who are not good about efforts to prevent cervical cancer is 11 respondents (22%). Young women in Class X of Dharma Bakti Private High School, Tanah Jawa, Simalungun Regency are able to know how to prevent cervical cancer, this is indicated by 42 respondents (84%) trying to stay away from the causes of cervical cancer and are able to prevent it, but there are still 8 respondents (16%) who do not know the efforts to prevent cervical cancer. The level of knowledge of young women with efforts to prevent cervical cancer in Class X of Dharma Bakti Private High School, Tanah Jawa, Simalungun Regency has a significant relationship where there is a chi square test result, namely ρ <0.05 (0.01).